The Effect of Job Demand, Work-life Balance, and Organizational Commitment on Employee Performance in Employee Class Students of the Faculty of Economics at Mercu Buana University Yogyakarta - Khoeriyah, Nisa Ul; Widarta , Widarta (Indonesian Journal Publisher, 2024)
The purpose of this study is to determine the influence of job demand, work-life balance, and organizational commitment on employee performance in the Employee Class of the Faculty of Economics at Mercu Buana University Yogyakarta.The sample determination technique used is non-probability purposive sampling, with the criteria of active students of the Faculty of Economics, Mercu Buana University Yogyakarta for the class of 2020, 2021, and 2022 and have undergone dual roles namely studying by working for at least one year. In this study, 80 respondents were used. The results of the instrument test stated that all statement items were declared valid and reliable. The analysis techniques used are classical assumption analysis, multiple regression analysis and hypothesis testing. The results of this study show that Job demand and work-life balance have a positive and significant effect on employee performance, organizational commitment does not have a significant effect on employee performance, and simultaneously Job demand, work-life balance, and organizational commitment have a positive and significant effect on employee performance Keywords: job demand, work-life balance, organizational commitment, kinerja Karyawan